National Distribution Project and Pardus Operating System - Karakoç, Mehmet Mehdi; Varol, Asaf (Fırat University, 2016)
In 2003, the Scientific and Technological Research Council of Turkey (TUBITAK) commissioned the National Research Institute of Electronics and Cryptology (UEKAE) in order to research feasibility of a national operating system for dependence from foreign countries. This project is called as National Distribution (Ulusal Dağıtım). In 2005, the project published its first product, which is called as Pardus 1.0. In this study, Pardus Operating System has been introduced. The current development status, versions, usage, advantages and limitations of the Pardus operating system have been investigated

Türkiye Bilimsel ve Teknik Araştırma Kurumu (TÜBİTAK), 2003 yılında Ulusal Elektronik ve Kriptoloji Araştırma Enstitüsünü (UEKAE) dışa bağımlılıktan kurtulmak için bir milli işletim sisteminin yazılabilirliğini araştırmak üzere görevlendirdi. Bu proje Ulusal Dağıtım diye adlandırıldı. Yapılan çalışmalar sonucu 2005 yılında bu ekip Pardus 1.0 adıyla ilk ürününü piyasaya sürdü. Bu çalışmada işletim sistemleri ile ilgili temel kavramlar verildikten sonra Linux İşletim Sistemi anlatılmakta ve ardından Pardus İşletim Sistemi üzerinde durulmaktadır.
Ulusal Dağıtım Projesi ve Pardus İşletim Sistemi